The practice of social research - Babbie, Earl R. (Belmont, Calif : Wadsworth Cengage, 2010)
This is a comprehensive, straightforward introduction to the field o f research as practiced by social scientists. This best-selling book em phasizes the research process by demonstrating how to design research s tudies, introducing the various observation modes in use today, and ans wering questions about research methods--such as how to conduct online surveys, and analyze both qualitative and quantitative data. The practi ce of social research provides all the tools researchers and consumers need to apply social research.
Includes bibliographic references and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology